Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus